Procedings of the Development of Social Farestry and Sustainable forest management held in Yogyakarta August 29 September 1994 in cooperation between perhutani and the Faculty of forestry Gadjah Mada University - Seminar on the Development of Social Farestry and Sustainable forest management (Perum Perhutani, 1994)
xii, 297 p. : il.; 24 cm.